A contemporary TOC innovative thinking process in the backdrop of leagile supply chain. Issue 3 (11th April 2016) - Banerjee, Arnab; Mukhopadhyay, Saroj Kumar
Abstract : Purpose: – The purpose of this paper is to propose a fresh perspective to effectively adopt leagility in supply chain. The research adopts Theory of Constraints (TOC) methodology and amalgamates it with design thinking process, people's opinion and mathematical approach to help achieve supply chain leagility. Design/methodology/approach: – The proposed framework is a seven stepped approach to achieve supply chain leagility combination analytical and mathematical procedures. Data enveloping analysis (DEA) is used to identify high level constraint. The new designed thinking process is used to further evaluate the constraints. Nominal group technique (NGT) is used to help build the current reality tree and identify detail level constraints. Findings: – The framework application on a case supply chain improves various parameters of leanness and agility over a period of one year. Improvements include reduced rework, improved cash flow, reduced operating cost, reduced order backlog and better customer interaction. Research limitations/implications: – This research opens up TOC application in a totally new area of leagility adoption in supply chain. The framework needs to be explored with more implementation in various business scenarios. Practical implications: – The proposed framework is extremely intuitive and pragmatic in approach. The case application demonstrates the framework can be easily adopted by supply chain managers to improve leagility. Social implications: – The current study attempts to diversify the TOC application. Using thinking process, DEA and NGT in TOC parlance brings in objectivity and employees together for improvement. Originality/value: – Amalgamating the mathematical approach of DEA, design thinking process and NGT within the TOC framework for supply chain leagility is new and novel.